Tinjauan Yuridis Ditolaknya Pernyataan Pailit Atas Dasar Perlakuan Yang Sama Pada Anak Perusahaan BUMN - Robert; Mahmul Siregar; Siallagan, Agnes Angelina (Acta Law Journal, 2023)
BUMN in carrying out restructuring carry out the principle of holding companies in maximizing capital. The legal relationship established in the application of the holding company principle between the parent company and its subsidiaries is caused by the takeover of shares by the parent company. BUMN subsidiaries are treated the same as BUMN by fulfilling several conditions as specified in Article 2A paragraph (7) of PP RI Number 72 of 2016. This research is focused on analyzing and analyzing problems related to the legal status of BUMN subsidiaries according to Indonesian law, legal provisions regarding the legal relationship of BUMN holding companies to BUMN subsidiaries filed for bankruptcy, and analysis of the rejection of bankruptcy applications based on equal treatment of BUMN subsidiaries in Decision Number 35/Pdt.Sus-Pailit/2021/PN. Niaga.Jkt.Pst. The research method used is a normative research method that is descriptive. Data sources were obtained through primary, secondary, and tertiary legal materials. The data collection technique used is a literature study. This normative research is based on qualitative analysis of secondary data in the form of laws and regulations and library materials. To prevent various interpretations regarding the limitation of bankruptcy application authority for BUMN subsidiaries engaged in the public interest sector, it is necessary to have clear arrangements. Currently, the Bankruptcy Law has not explicitly regulated the authority to apply for bankruptcy, especially for state-owned companies that adopt a holding system, so it is necessary to make changes or additions to the regulations. In Decision Number 35/Pdt.Sus-Bankruptcy/2021/PN.Niaga.Jkt.Pst the judge did not consider the aspect of share ownership of the bankruptcy respondent and its source of capital that must be owned entirely by the state against BUMN subsidiaries that are treated the same as BUMN engaged in the public interest when referring to Article 2 paragraph (5) of UU KPKPU.